Determining genetic similarities and relationships among cowpea breeding lines and cultivars by microsatellite markers - Li, C.; Fatokun, C.A.; Ubi, B.; Singh, B.; Scoles, Glen A. (Wiley, 2001)
Cowpea [Vigna unguiculata (L.) Walp] is an important grain legume crop grown for its protein rich grains. It is an inexpensive source of protein in the diets of people in sub-Saharan Africa. The International Institute of Tropical Agriculture (IITA) has been working on the improvement of cowpea for more than 30 yr. Over 60 countries receive cowpea cultivars improved by IITA for testing and adoption where needed. Many of these cultivars have identical parentage but look very different morphologically when grown in the field. Forty-six microsatellite DNA markers were used to evaluate genetic similarities among 90 cowpea breeding lines developed at IITA. Twenty-seven primer pairs could amplify polymorphic single-locus microsatellites from all of these materials. Two to seven alleles per primer were detected with a polymorphic information content varying from 0.02 to 0.73. By means of only five polymorphic microsatellite primers, 88 of the 90 cowpea lines could be distinguished. A dendrogram based on the microsatellite polymorphisms generally agreed with the pedigree of the cowpea lines.